2012
DOI: 10.3856/vol40-issue1-fulltext-25
|View full text |Cite
|
Sign up to set email alerts
|

Dieta de Hatcheria macraei (Girard, 1855) (Teleostei, Siluriformes, Trichomycteridae) en el rio Chubut, Argentina

Abstract: Dieta deHatcheria macraei (Girard, 1855) (Teleostei, Siluriformes, Trichomycteridae) en el río Chubut, Argentina

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The diversity and width of the rainbow trout diet observed in this study is similar to that reported for this Table 3 Selectivity index (Ivlev) of prey in the diet of rainbow trout (Oncorhynchus mykiss) (Arismendi et al 2012;Di Prinzio et al 2013) but higher than the observed in the native catfish Hatcheria macraei (Ferriz 1994(Ferriz , 2012Barriga et al 2009;Di Prinzio and Casaux 2012). This fact supports the proposal by Di Prinzio et al (2013) indicating that the expansion success of the rainbow trout in Patagonia could be explained, among other factors, by their high feeding plasticity, which depends on different issues (prey-type characteristics, seasonal changes in resource supply, food-habitat utilization, etc.).…”
Section: Discussionsupporting
confidence: 86%
“…The diversity and width of the rainbow trout diet observed in this study is similar to that reported for this Table 3 Selectivity index (Ivlev) of prey in the diet of rainbow trout (Oncorhynchus mykiss) (Arismendi et al 2012;Di Prinzio et al 2013) but higher than the observed in the native catfish Hatcheria macraei (Ferriz 1994(Ferriz , 2012Barriga et al 2009;Di Prinzio and Casaux 2012). This fact supports the proposal by Di Prinzio et al (2013) indicating that the expansion success of the rainbow trout in Patagonia could be explained, among other factors, by their high feeding plasticity, which depends on different issues (prey-type characteristics, seasonal changes in resource supply, food-habitat utilization, etc.).…”
Section: Discussionsupporting
confidence: 86%
“…The food habits of the native torrent catfish agree with the bentophagous type, and the dominant preys are chironomid larvae (Chironomidae family, Diptera), caddisflies larvae (Or. Trichoptera), and cladocerans in the freshwater environments of the southern Andes [43].…”
Section: Discussionmentioning
confidence: 99%
“…El régimen alimentario tanto para H. macraei como para O. mykiss en el arroyo El Carrizal de las Burras fue del tipo carnívoro-generalista. H. macraei depreda preferentemente insectos y anélidos, mientras que en poblaciones de la Patagonia la dieta se complementa con crustáceos y algas (Barriga & Battini, 2009;Ferriz, 2012).…”
Section: H Macraei Desarrolló Todo Su Ciclo De Vida En Los Ambientes ...unclassified
“…Las presas principales en la dieta de H. macraei fueron las larvas de Chironomidae, en coincidencia con lo registrado para poblaciones de Patagonia (Barriga & Battini, 2009;Ferriz, 2012), a excepción del río Limay donde las ninfas de Ephemeroptera y larvas de Trichoptera fueron las más abundantes (Ferriz, 1994). El solapamiento de dietas se observó entre todos los estadios de desarrollo, las larvas de Chironomidae fueron las más frecuentes (%F) y abundantes (%N) en todos los estadios y de mayor volumen (%V) en machos y juveniles.…”
Section: H Macraei Desarrolló Todo Su Ciclo De Vida En Los Ambientes ...unclassified
See 1 more Smart Citation